CORPORATE FINANCIAL PERFORMANCE, CORPORATE ENVIRONMENTAL PERFORMANCE, CORPORATE SOCIAL PERFORMANCE AND STOCK RETURN - Machdar, Nera Marinda (Jurnal Manajemen dan Kewirausahaan, 2017)
The purpose of this study is to examine the influence of corporate financial performance, corporate environmental performance and corporate social performance on the stock return. The study used 22 companies/ firms’ financial statements for the period 2009 to 2015. The results show that: (a) corporate financial performance influences positively stock return. It means that investors pay more attention to marketbased measures over accounting-based measures; (b) corporate environmental performance influences negatively stock return. This indicates that investors do not consider the relative environmental choices of the companies or that stock market does not like hearing about the environmental news, and (c) corporate social performance does not influence stock return. This is probably because investors are not interested in the social news. There are other data that can be obtained as a consideration in the decision making.